Manajemen Program Kelas Unggulan untuk Meningkatkan Citra Madrasah Tsanawiyah 1 Kabupaten Madiun - Lukman Hakim (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo (previously known as IAIN Ponorogo), 2021)
The world of education enters this global era with all its advantages and challenges. Under conditions of harsh competition like this, the role of a strong image will be increasingly important for service providers in winning competition. It is in this context that Islamic education institutions carry out strategies to improve the image of madrasah. Madrasah Tsanawiyah 1 Kabupaten Madiun has held the superior class program to improve the madrasah’s image. Based on the process of collecting and analyzing data, researchers produce: (1) Management of a superior class program to improve the image of madrasah in MTsN 1 Madiun Regency, that is: Planning (objectives, programs, budgets). Organizing (organizational structure, educators, students, materials, infrastructure, costs). Implementation (Before teaching, Teaching and After teaching). Evaluation (Formative, Summative, Test and Non-test). (2) obstacles: (a) Planning: Limited budget, Depends on parents' contributions. (b) Organizing: Special curriculum has not yet been realized, Allocation of learning hours, The lack of teaching staff. (c) Implementation: The existence of ups and downs, clash with other importances, facilities that are not quickly met, Limited guidance time, Clash schedule, Test season, Rainy season, Students are not proportional to the number of teachers and teachers have not maximally applied IT based learning. (d) Evaluation: There are changes in report cards from manual to ARD, Not all teachers understand about IT and the limited facilities for evaluation. (3) The Implications of Management of a Superior Class Programs include: Having good quality, many achievements, excellence in science and technology and Faith and piety, good, advanced and favorite schools and Having the facilities to develop students' abilities, talents and interests. Keywords: management, superior class program, image of madrasah